2003
DOI: 10.1080/00016350310005844
|View full text |Cite
|
Sign up to set email alerts
|

Dental anxiety in Iceland: an epidemiological postal survey

Abstract: In this study, we examined the prevalence of specific (dental) phobia among a sample of the Icelandic population. In addition to dental anxiety we explored factors that could be related to dental anxiety. In the period 1972-73, a stratified sample of 1641 schoolchildren in Reykjavík was selected for a study on malocclusion, dental maturation and other factors. Twenty-two years later (1995), a postal survey conducted in this group looked at many variables relating to oral health, including orofacial pain, funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…In this study, participants who were afraid of visiting a dentist were evaluated at two different points in time: in 2000 and in 2011, but how afraid of visiting a dentist they were between these surveys is not known. However, women were more afraid of visiting a dentist than men were, as also reported in earlier studies , but changes in being afraid of visiting a dentist were similar among men and women.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, participants who were afraid of visiting a dentist were evaluated at two different points in time: in 2000 and in 2011, but how afraid of visiting a dentist they were between these surveys is not known. However, women were more afraid of visiting a dentist than men were, as also reported in earlier studies , but changes in being afraid of visiting a dentist were similar among men and women.…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of dental fear varies according to gender and age. In cross‐sectional studies, women have consistently reported dental fear more often than men , but according to age, the results were less consistent . There seem to be differences in changes over time by gender and age.…”
mentioning
confidence: 94%
“…2 While socio-economic gradients are rife in relation to health outcomes, there is less evidence of differences in dental fear by socio-economic status. In general, it appears that people from lower socio-economic backgrounds have higher fear, 18,22,23 although some studies have failed to find a relationship between education and dental fear. 6,20 There is also evidence that socio-economic status may be related only to moderate levels of dental anxiety.…”
Section: S C I E N T I F I C a Rt I C L Ementioning
confidence: 99%
“…6 Others have found that women are more likely to exhibit dental anxiety, which was most often attributed to a negative dental experience. [7][8] Although the literature includes suggestions for combating dental anxiety (for example, establishing trust, appropriate attire, making pharmacological support available), [9][10] the bulk of the research on this topic documents such anxiety rather than addresses how to ease it.…”
Section: Reported Causes Of Patient Anxiety and Painmentioning
confidence: 99%